A Plasma Protein Network Regulates PM20D1 and N-Acyl Amino Acid Bioactivity. Issue 9 (17th September 2020) - Kim, Joon T.; Jedrychowski, Mark P.; Wei, Wei; Fernandez, Daniel; Fischer, Curt R.; Banik, Steven M.; Spiegelman, Bruce M.; Long, Jonathan Z.
Summary: N-acyl amino acids are a family of cold-inducible circulating lipids that stimulate thermogenesis. Their biosynthesis is mediated by a secreted enzyme called PM20D1. The extracellular mechanisms that regulate PM20D1 or N-acyl amino acid activity in the complex environment of blood plasma remains unknown. Using quantitative proteomics, here we show that PM20D1 circulates in tight association with both low- and high-density lipoproteins. Lipoprotein particles are powerful co-activators of PM20D1 activity in vitro and N-acyl amino acid biosynthesis in vivo . We also identify serum albumin as a physiologic N-acyl amino acid carrier, which spatially segregates N-acyl amino acids away from their sites of production, confers resistance to hydrolytic degradation, and establishes an equilibrium between thermogenic "free" versus inactive "bound" fractions. These data establish lipoprotein particles as principal extracellular sites of N-acyl amino acid biosynthesis and identify a lipoprotein-albumin network that regulates the activity of a circulating thermogenic lipid family. Graphical Abstract: Highlights: The N-acyl amino acid biosynthetic enzyme PM20D1 is localized to lipoproteins Lipoproteins co-activate PM20D1 activity and N-acyl amino acid biosynthesis Serum albumin is a physiologic plasma carrier for N-acyl amino acids Albumin determines an equilibrium between active versus inactive N-acyl amino acids Abstract : N-acyl amino acids are a family of lipid hormones that stimulate thermogenesis. Kim et al. uncover lipoprotein particles as sites for N-acyl amino acid biosynthesis and serum albumin as a physiologic N-acyl amino acid carrier. These highly abundant plasma proteins regulate the metabolism and bioactivity of a circulating lipid family.